Deradicalism in The Family at Tahuna, Sangihe Islands, North Sulawesi - Rajafi, Ahmad; Yetta, Yasin; Lasido, Nur Allan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study aimed to examine the deradicalism in the family at Tahuna on Sangihe Islands, North Sulawesi with the potential to raise radicalism. This area is the transmission line for terrorists to Indonesia from Mindanao. Furthermore, the entry of transnational Islam emphasizes religious textuality and intolerance of others. This study is a type of empirical legal research, namely a legal research method taken from the facts that exist in the Tahuna Muslim community. The data was collected using observation, interviews, and documentation and analyzed through the maqashid al-shari'a approach. The result was expected to help prevent family radicalism, and mobilize women's majlis taklim in mosques at the Tahuna area in each recitation. Furthermore, they could help transfer moderate Islamic ideas emphasizing discussing hifzh al-nafs and hifzh al-nasl, especially in family partnerships in the family. This would ensure women or wives are no longer subordinated to men and the tolerance values inculcated among people of the same and different religions. In general, the tolerance values are transferred through local wisdom adages in the Sangihe Islands, including mepalose and pantuhu makasalentiho somahe kai kehage, as reinforcement of family deradicalism.